Enhanced photoelectrochemical performance and photocatalytic activity of ZnO/TiO2 nanostructures fabricated by an electrostatically modified electrospinning - Ramos, PG (2017)
ZnO/TiO2 nanostructures were fabricated by an electrostatically modified electrospinning technique using zinc acetate and commercially available TiO2-P25, polyvinyl alcohol, and a solvent. It was found that the TiO2-P25 nanoparticles were attached to the ZnO nanostructures, and the mean diameter of the nanoparticles forming the nanostructures ranged from 31 to 52 nm with increasing the amount of zinc acetate. The obtained results evidenced that the coupling of TiO2 with ZnO enhanced the IPCE and improved the photocatalytic activity of ZnO. Particularly, the ZnO/TiO2 nanostructures fabricated with a zinc acetate-to-PVA ratio of 2:3 exhibited the highest IPCE and photocatalytic activity.